LncRNA KCNQ1OT1 knockdown inhibits viability, migration and epithelial-mesenchymal transition in human lens epithelial cells via miR-26a-5p/ITGAV/TGF-beta/Smad3 axis. (November 2020) - Liu, Jiajia; Dong, Yiran; Wen, Yuechun; Shi, Lei; Zhu, Zicheng; Ke, Genjie; Gu, Yonghao
Abstract: Background: Long noncoding RNA potassium voltage-gated channel subfamily Q member 1 opposite strand/antisense transcript 1 (KCNQ1OT1) takes part in diabetic cataract progression. This research aims to analyze the function and mechanism of KCNQ1OT1 on viability, migration and epithelial-mesenchymal transition (EMT) in lens epithelial cells. Methods: 20 diabetic cataract posterior lens capsule tissues and normal samples were collected. Lens epithelial cells (SRA01/04) were stimulated via high glucose (HG). The levels of KCNQ1OT1, miR-26a-5p, integrin αV (ITGAV), TGF-β, Smad3 and phosphorylated (p)-Smad3 were measured via quantitative real-time polymerase chain reaction or Western blot. Cell viability, migration and EMT were analyzed via MTT, wound healing, transwell and Western blot assays. The target relationship between miR-26a-5p and KCNQ1OT1 or ITGAV was determined via luciferase reporter assay. Results: KCNQ1OT1 was up-regulated and miR-26a-5p level was reduced in diabetic cataract tissues and HG-treated SRA01/04 cells. Silence of KCNQ1OT1 or miR-26a-5p up-regulation repressed cell viability, migration and EMT in SRA01/04 cells stimulated via HG. KCNQ1OT1 could target miR-26a-5p and controlled cell viability, migration and EMT via regulating miR-26a-5p. ITGAV was targeted via miR-26a-5p and positively regulated via KCNQ1OT1. ITGAV overexpression promoted cell viability, migration and EMT in HG-treated SRA01/04 cells, which were mitigated by KCNQ1OT1 silence. KCNQ1OT1 knockdown mitigated HG-induced the activation of TGF-β/Smad3 signaling by regulating miR-26a-5p. Conclusion: KCNQ1OT1 knockdown represses cell viability, migration and EMT through miR-26a-5p/ITGAV/TGF-β/Smad3 axis in SRA01/04 cells under HG condition, providing a new target for the treatment of diabetic cataract. Highlights: KCNQ1OT1 expression was increased in diabetic cataract tissues and high glucose-treated SRA01/04 cells. KCNQ1OT1 regulated cell viability, migration and epithelial-mesenchymal transition by targeting miR-26a-5p. ITGAV promoted cell viability, migration and epithelial-mesenchymal transition in high glucose-treated SRA01/04 cells.